2017
DOI: 10.1136/bmjopen-2016-015257
|View full text |Cite
|
Sign up to set email alerts
|

Dementia-friendly interventions to improve the care of people living with dementia admitted to hospitals: a realist review

Abstract: ObjectivesTo identify features of programmes and approaches to make healthcare delivery in secondary healthcare settings more dementia-friendly, providing a context-relevant understanding of how interventions achieve outcomes for people living with dementia.DesignA realist review conducted in three phases: (1) stakeholder interviews and scoping of the literature to develop an initial programme theory for providing effective dementia care; (2) structured retrieval and extraction of evidence; and (3) analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 56 publications
2
109
0
1
Order By: Relevance
“…Some studies have found that CO practices may be harmful for patients and the sitters themselves, highlighting the urgent need to better understand the role of sitters . A recent review from the United Kingdom on dementia‐friendly interventions to improve the care of people with dementia admitted to hospitals highlights that educational interventions should focus on person‐centered care and opportunites for staff to share their experiences addressing behavioral and psychological symptoms . Our intervention supports this finding by providing extensive didactic and hands‐on training for PES and staff education.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies have found that CO practices may be harmful for patients and the sitters themselves, highlighting the urgent need to better understand the role of sitters . A recent review from the United Kingdom on dementia‐friendly interventions to improve the care of people with dementia admitted to hospitals highlights that educational interventions should focus on person‐centered care and opportunites for staff to share their experiences addressing behavioral and psychological symptoms . Our intervention supports this finding by providing extensive didactic and hands‐on training for PES and staff education.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, PaWD find the acute care environment unusual because medical treatment is the highest priority, and an environment filled with medical equipment can make PaWD uncomfortable. Nurses develop a positive, home-like, friendly FIGURE 1 Literature review flowchart atmosphere to facilitate interconnections with PaWD (Borbasi et al, 2006;Haak, 2009;Handley, Bunn, & Goodman, 2017;Hynninen et al, 2014;Page & Hope, 2013;Rushton et al, 2016). Furthermore, nurses play a role in setting a social environment that provides social resources to connect PaWD with their communities; this can improve PaWD's daily lives in their communities after discharge (Borbasi et al, 2006;de Vries, 2013;Hynninen et al, 2014;Josefsson et al, 2008;Luke et al, 2008;Tan et al, 2017).…”
Section: Coordinating External Environmentsmentioning
confidence: 99%
“…Knowledge of the theoretical underpinnings of dementia allows nurses to apply and progress the competency (Chang et al, 2009;Chater & Hughes, 2012;Handley et al, 2017;Tan et al, 2017) and can help nurses obtain better information on providing appropriate dementia nursing care (Elliot & Adams, 2011). Further, as clinical specialists, the knowledge is also required to continually progress through levels of clinical expertise-from novice, through to expert-which is associated with improving the quality of dementia nursing care (Borbasi et al, 2006;Chater & Hughes, 2012;Crabtree & Mack, 2010;Elliot & Adams, 2011;Handley et al, 2017;Iliffe et al, 2010;Josefsson et al, 2008;Lin et al, 2012).…”
Section: Building Theoretical and Clinical Knowledgementioning
confidence: 99%
“…Effective approaches to make sustainable change are needed. Research indicates that training alone is not sufficient to influence staff to change practice (Handley, Bunn, & Goodman, ). Hospital staff need protected times and spaces for continuous team learning and knowledge adaption (Hung, Phinney, Chaudhury, & Rodney, ).…”
Section: Introductionmentioning
confidence: 99%